“DEMISTIFIYING” PURITANISM IN ISLAMIC LAWS - Abid Rohmanu (IAIN Tulungagung, 2018)
This paper aims to evaluate puritanism in formulating Islamic laws through the lens of prophetic social science approach. The prophetic social science approach, as an Indonesian historian Kuntowijoyo argues, offers a new perspective in understanding the position of religion in society. It calls for theoanthropocentric, in contrast to theocentric, approach to study religion, thus suggesting a contextualized interpretation of religion. This approach is essential in formulating Islamic laws, while reserving also as a criticism to theocentricism that leads to Islamic puritanism. This article will contribute to the discussion on Islamic legal paradigm as epistemic field as to which theoanthropocentrical reserves as analytical tool to demystify puritanism in formulating Islamic law. In so doing, the article offers to essential elements of formulating Islamic laws: the transformation from theocentric to theoanthropocentric approach and the contextualization of Islamic laws.